Pemasaran Dodol Mangrove Melalui Digital Marketing di Desa Wisata Pulau Pahawang - Evi Meidasari M; Hairudin Hairudin; Destoprani Brajanoto; Yudhinanto CN (Institut Teknologi dan Bisnis Semarang, 2023)
Marketing activities have a very important role in the business world, because the marketing of a product or service in a company affects the profit earned by the company. Therefore, marketers also compete with each other to create goods or services that are as attractive as possible in order to attract customer interest in the products or services produced. Because marketing begins with meeting human needs which then grows into human desires.the potential in the culinary field, namely Dodol Mangrove, is still experiencing deficiencies in terms of production and packaging processes, due to the lack of public knowledge of good packaging so that the resulting products can expand outside Pahawang Island and are widely known by the people of Lampung in particular.